2012
DOI: 10.1016/j.anaerobe.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Synergy in biofilm formation between Fusobacterium nucleatum and Prevotella species

Abstract: Japan Running title: F. nucleatum-Prevotella species CoaggregationThe aim of this study was to characterize the role of coaggregation between Fusobacterium nucleatum and Prevotella species in biofilm formation. Materials and Methods:ATCC and clinically isolated strains of F. nucleatum, P.intermedia and P. nigrescens were subjected. Coaggregation between these species was determined by visual assay. Biofilm formation was assessed by crystal violet staining. Effect of co-culture of F. nucleatum with Prevotella s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 49 publications
2
52
0
1
Order By: Relevance
“…Other species such as Fusobacterium which also do not adhere well to vaginal epithelial cells [44], are able to facilitate co-aggregation between species such as Prevotella [103] and Bifidobacterium [104] in polymicrobial infections [105,106] by acting as a bridge between early and late colonisers in biofilm formation [107,108,109] and by supporting the growth of obligate anaerobes such as Porphyromonas , [110,111] in aerated and carbon dioxide depleted environments [110,111,112]. By adhering to other vaginal microbes [113], F. nucleatum is able to mask the surface components that are recognized by H 2 O 2 -producing lactobacilli and prevent detection by antagonistic microflora thus allowing for its integration into the developing vaginal microbial community associated with BV [114].…”
Section: Resultsmentioning
confidence: 99%
“…Other species such as Fusobacterium which also do not adhere well to vaginal epithelial cells [44], are able to facilitate co-aggregation between species such as Prevotella [103] and Bifidobacterium [104] in polymicrobial infections [105,106] by acting as a bridge between early and late colonisers in biofilm formation [107,108,109] and by supporting the growth of obligate anaerobes such as Porphyromonas , [110,111] in aerated and carbon dioxide depleted environments [110,111,112]. By adhering to other vaginal microbes [113], F. nucleatum is able to mask the surface components that are recognized by H 2 O 2 -producing lactobacilli and prevent detection by antagonistic microflora thus allowing for its integration into the developing vaginal microbial community associated with BV [114].…”
Section: Resultsmentioning
confidence: 99%
“…T. denticola and T. forsythia have fastidious growth requirements for culture [6,11]. Several bacterial pairs were reptorted to required cell to cell contact for enhancement of biofilm formation [41,42]. Taken together with these reports, the coaggregation reaction between T. denticola and T. forsythia may work for adhesion and colonization to dental plaque and involve the increase of T. denticola or T. forsythia in dental plaque.…”
Section: Discussionmentioning
confidence: 62%
“…The synergy biofilm formation by Prevotella spp. and other bacteria such as Fusobacterium nucleatum (Okuda et al, 2012) and Porphyromonas (Henry et al, 1996) has been previously reported.…”
Section: Biofilm Formationmentioning
confidence: 99%